2019
DOI: 10.1016/j.ssmph.2019.100465
|View full text |Cite
|
Sign up to set email alerts
|

Work-family conflict, self-reported general health and work-family reconciliation policies in Europe: Results from the European Working Conditions Survey 2015

Abstract: The increasing labor market participation of women in Europe leads to many women and men having to reconcile paid work with family work and thus reporting work-family conflict (WFC). WFC is related to different dimensions of health. In the present article, we analyzed the role different reconciliation policies among European countries may play regarding WFC and its association with self-reported health. The analyses are based on data from Eurofound's European Working Conditions Survey 2015. The work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
6
21
0
Order By: Relevance
“…Our analyses are the first to show that parents with high WTFC living in Germany report significantly poorer self-reported general health than mothers and fathers with low WTFC. This confirms results from European and U.S.-American studies in which high WTFC was associated with poorer self-reported general health [16,38]. Considering WTFC as a source of stress, the results are consistent with stress process theory [13,14], which argues that stress is a significant predictor of individual health.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our analyses are the first to show that parents with high WTFC living in Germany report significantly poorer self-reported general health than mothers and fathers with low WTFC. This confirms results from European and U.S.-American studies in which high WTFC was associated with poorer self-reported general health [16,38]. Considering WTFC as a source of stress, the results are consistent with stress process theory [13,14], which argues that stress is a significant predictor of individual health.…”
Section: Discussionsupporting
confidence: 87%
“…The results also implicate no gender differences in direction and strength regarding the association of WTFC and health. This is in line with an internationally growing number of studies that do not show differences in health-related consequences of WTFC by gender [38]. On the other hand, this seems remarkable against the background of the different work-and family-related circumstances mothers and fathers are facing in Germany.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…After more than a year of restrictions, the well-being of citizens in general, and teachers particularly, has been affected according to different studies [2][3][4]. In this regard, although efforts have been made to train teachers through online learning platforms, and work-family reconciliation has been [5], this modal change implied a series of challenges when developed in a hostile, complex and unprecedented context [6]. Therefore, it is necessary to develop sustainable work environments and policies, which provide well-being to teachers in different aspects (social, emotional, physical), which would be reflected not only in the improvement of their productivity-even in extreme situations, as is the case of job development during the COVID-19 pandemic [7][8][9]; it would also help to prevent pathologies associated with the teaching function, such as burnout due to prolonged exposures of stress, factors and individual characteristics [10], such as age and years of experience [11,12], gender of teachers [13,14] and poorly or unsustainable working conditions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, self-rated health was widely used in social science research. So far, there is a considerable bulk of research studied the attributes of W_F_Cs [14][15][16][17][18] and linked W_F_Cs to poor self-rated health of community dwellers [8,11] and working populations [12,[19][20][21]. The literature indicated vast variabilities in the W_F_Cs' levels and their correlates, the proportions of subjects with poor self-rated health, and the magnitude of association between these con icts and self-rated health across different cultures and populations.…”
Section: Introductionmentioning
confidence: 99%